How Kenyan Potato Farmers Evaluate the Seed: Implications for the Promotion of Certified Seed Potato - Atieno, E.; Kilwinger, Fleur B.M.; Almekinders, Conny J.M.; Struik, P.C. (Springer, 2023)
Improving the quality of seed potatoes that smallholder farmers plant continues to represent one of the most important challenges of the potato sector in most developing countries to counter the long-lasting poor yields. This study aimed to better understand the way farmers choose seed potato by exploring the attributes they look for and the benefits they expect from them. We used means-end chains analysis in combination with Kelly’s repertory grid as an elicitation technique and disaggregated data for male and female partners. In total, farmers named 38 attributes they look for when selecting seeds. Farmers associate “good” seeds to those that are well-sprouted, have many eyes, are of a variety they know, are medium in size, are certified, and are undamaged. Most preferred attributes lead to a higher yield and consequently higher income which is the most predominant avenue for farmers to achieve their desired values in life. Female farmers mentioned fewer attributes and also pursued fewer values than their male counterparts. Users and non-users of certified seed were shown to use the same attributes to select their potato seeds. Non-users of certified seed thus seem to be aware of the benefits of certified seed even though they are not using it. The results from this study indicate that increasing the availability of certified seed is not necessarily a straightforward way of improving the quality of seed potato planted by Kenyan smallholder farmers.